2020
DOI: 10.6018/analesps.402111
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Hardiness and optimism on negative life events and coping self-efficacy in first-year undergraduate students

Abstract: Introducción: Este estudio analiza el papel de la resistencia y el optimismo en los eventos negativos de la vida y la autoeficacia de afrontamiento en 228 estudiantes universitarios de primer año de la Universidad de Lorestan (Irán). El objetivo del estudio era doble: (1) analizar las asociaciones entre resistencia, optimismo, eventos de vida negativos y autoeficacia de afrontamiento; y (2) determinar si la resistencia y el optimismo moderan la relación entre los eventos negativos de la vida y la autoeficacia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…The findings are similar to the results of the study conducted by Abbasi et al (2020) on "Moderating effects of resilience and optimism on negative life events and coping self-efficacy in undergraduate first-year students". The results revealed that there is a significant relationship between Hardiness, optimism, negative life events and coping self-efficacy.…”
Section: Variablessupporting
confidence: 88%
“…The findings are similar to the results of the study conducted by Abbasi et al (2020) on "Moderating effects of resilience and optimism on negative life events and coping self-efficacy in undergraduate first-year students". The results revealed that there is a significant relationship between Hardiness, optimism, negative life events and coping self-efficacy.…”
Section: Variablessupporting
confidence: 88%
“…Memiliki sikap optimisme individu akan terhindar dari depresi dan apatis yang berkepanjangan, sehingga individu akan merasa lebih bahagia, mampu berpikir jernih, dan dampaknya adalah tercipta rasa nyaman (Harpan, 2015). Seseorang yang memiliki sikap optimis akan cenderung memiliki harapan yang positif terhadap masa depan (Abbasi, Ghadampour, Hojati, & Senobar, 2020). Seseorang yang optimis juga akan membawa mereka untuk berusaha lebih keras dalam mewujudkan masa depannya meskipun mengalami kesulitan (Musabiq & Meinarno, 2017).…”
Section: Sig (P) Keteranganunclassified
“…Self‐efficacy refers to an individual's perception that he or she has the ability to effectively reduce or control threats (Rotter, 1992), which is positively related to disaster preparedness (Becker et al, 2013; Lindell & Whitney, 2000). Recent empirical studies have indicated that optimists who are convinced that what they do will pay off possess a high level of self‐efficacy (Abbasi et al, 2020; Biron et al, 2020), which makes them tend to believe that they possess the ability of preparedness and that this preparedness is effective. Moreover, existing studies on coping strategies hold that optimists may gain an advantage when dealing with dilemmas (including earthquakes) from their proactive coping strategies, such as solving problems and seeking social support (Carver et al, 1989, 2010; Fontaine et al, 1993; Scheier et al, 1986).…”
Section: Theoretical Model and Research Hypothesesmentioning
confidence: 99%
“…In the past two decades, there has been a consensus that optimism is an individual variable that reflects the extent to which people hold generalized favourable expectations for their future (Carver et al, 2010). Recent mainstream literature has continued to use this definition (Abbasi et al, 2020; Biron et al, 2020; Harris & Hahn, 2011). Thus, it can be considered that a person with a high level of optimism orientation has good expectations for his or her future.…”
Section: Theoretical Model and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation